Effects of modified tall oil on growth and body composition in adult ovariectomized rats - P R O'Quinn; S I Koo; S K Noh; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1999)
A trial was conducted to evaluate the effects of modified tall oil (MTO) on growth and body composition of adult ovariectomized rats. This trial was targeted as a model for postmenopausal women; thus, only data applicable to swine production are presented herein. Feeding MTO decreased adiposity, increased concentrations of certain lipids in tissues, increased vitamin E (octocopherol) levels in the adipose, and increased actual lean content. These data lend support to the carcass leanness and meat quality improvements routinely seen in swine from feeding MTO.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Rats; Modified tall oil; Vitamin E; Conjugated linoleic acid